All‐oral direct‐acting antiviral therapy against hepatitis C virus (HCV) in human immunodeficiency virus/HCV–coinfected subjects in real‐world practice: Madrid coinfection registry findings. Issue 1 (27th April 2018) - Berenguer, Juan; Gil‐Martin, Ángela; Jarrin, Inmaculada; Moreno, Ana; Dominguez, Lourdes; Montes, Marisa; Aldámiz‐Echevarría, Teresa; Téllez, María J.; Santos, Ignacio; Benitez, Laura; Sanz, José; Ryan, Pablo; et al.
Abstract : We evaluated treatment outcomes in a prospective registry of human immunodeficiency virus/hepatitis C virus (HCV)–coinfected patients treated with interferon‐free direct‐acting antiviral agent–based therapy in hospitals from the region of Madrid between November 2014 and August 2016. We assessed sustained viral response at 12 weeks after completion of treatment and used multivariable logistic regression to identify predictors of treatment failure. We evaluated 2, 369 patients, of whom 59.5% did not have cirrhosis, 33.9% had compensated cirrhosis, and 6.6% had decompensated cirrhosis. The predominant HCV genotypes were 1a (40.9%), 4 (22.4%), 1b (15.1%), and 3 (15.0%). Treatment regimens included sofosbuvir (SOF)/ledipasvir (61.9%), SOF plus daclatasvir (14.6%), dasabuvir plus ombitasvir/paritaprevir/ritonavir (13.2%), and other regimens (10.3%). Ribavirin was used in 30.6% of patients. Less than 1% of patients discontinued therapy owing to adverse events. The frequency of sustained viral response by intention‐to‐treat analysis was 92.0% (95% confidence interval, 90.9%‐93.1%) overall, 93.8% (92.4%‐95.0%) for no cirrhosis, 91.0% (88.8%‐92.9%) for compensated cirrhosis, and 80.8% (73.7%‐86.6%) for decompensated cirrhosis. The factors associated with treatment failure were male sex (adjusted odds ratio, 1.75; 95% confidence interval, 1.14‐2.69), Centers for Diseases Control and Prevention category C (adjusted odds ratio, 1.65; 95% confidence interval, 1.12‐2.41), a baseline cluster of differentiation 4–positive (CD4+) T‐cell count <200/mm 3 (adjusted odds ratio, 2.30; 95% confidence interval, 1.35‐3.92), an HCV RNA load ≥800, 000 IU/mL (adjusted odds ratio, 1.63; 95% confidence interval, 1.14‐2.36), compensated cirrhosis (adjusted odds ratio, 1.35; 95% confidence interval, 0.96‐1.89), decompensated cirrhosis (adjusted odds ratio, 2.92; 95% confidence interval, 1.76‐4.87), and the use of SOF plus simeprevir, SOF plus ribavirin, and simeprevir plus daclatasvir. Conclusion: In this large real‐world study, direct‐acting antiviral agent–based therapy was safe and highly effective in coinfected patients; predictors of failure included gender, human immunodeficiency virus–related immunosuppression, HCV RNA load, severity of liver disease, and the use of suboptimal direct‐acting antiviral agent–based regimens. (Hepatology 2018;68:32‐47).